A cluster of donor‐derived Cryptococcus neoformans infection affecting lung, liver, and kidney transplant recipients: Case report and review of literature. Issue 2 (12th February 2018) - Camargo, Jose F.; Simkins, Jacques; Schain, Denise C.; Gonzalez, A. Adrian; Alcaide, Maria L.; Anjan, Shweta; Guerra, Giselle; Roth, David; Kupin, Warren L.; Mattiazzi, Adela; Tan, Yaohong; Milikowski, Clara; et al.
Abstract: Donor‐derived infections (DDIs) are a very rare but potentially devastating complication of solid organ transplantation. Here we present a cluster of proven donor‐derived cryptococcal infection in the kidney, liver, and lung recipients from a single donor. Remarkably, the onset of illness in the kidney and liver recipients occurred more than 8‐12 weeks after transplantation, which is beyond the incubation period previously reported for donor‐derived cryptococcosis. DDI should always be considered in the differential diagnosis of transplant recipients admitted with febrile illness, even when presenting beyond the first month post‐transplant. Communication between reference laboratories, transplant centers, and organ procurement organizations is critical to improve outcomes.